Comparative analysis of gut microbiota following changes in training volume among swimmers - Hampton-Marcell, J. T.; Eshoo, T. W.; Cook, M. D.; Gilbert, J. A.; Horswill, C. A.; Poretsky, R. (International Journal of Sports Medicine, 2020)
Exercise can influence gut microbial community structure and diversity; however, the temporal dynamics of this association have rarely been explored. Here we characterized fecal microbiota in response to short term changes in training volume. Fecal samples, body composition, and training logs were collected from Division I NCAA collegiate swimmers during peak training through their in-season taper in 2016 (n=9) and 2017 (n=7), capturing a systematic reduction in training volume near the conclusion of their athletic season. Fecal microbiota were characterized using 16S rRNA V4 amplicon sequencing and multivariate statistical analysis, Spearman rank correlations, and random forest models. Peak training volume, measured as swimming distance, decreased significantly during the study period from 32.6±4.8 km/wk to 11.3±8.1 km/wk (ANOVA, p<0.05); however, body composition showed no significant changes. Coinciding with the decrease in training volume, the microbial community structure showed a significant decrease in overall microbial diversity, a decrease in microbial community structural similarity, and a decrease in the proportion of the bacterial genera Faecalibacterium and Coprococcus. Together these data demonstrate a significant association between short-term changes in training volume and microbial composition and structure in the gut; future research will establish whether these changes are associated with energy balance or nutrient intake.